2019
DOI: 10.1111/ggr.12298
|View full text |Cite
|
Sign up to set email alerts
|

High‐Precision, High‐Accuracy Oxygen Isotope Measurements of Zircon Reference Materials with the SHRIMP‐SI

Abstract: Analytical protocols for SHRIMP‐SI oxygen isotope analysis (δ18O) of a suite of zircon reference materials (RMs) are presented. Data reduction involved a robust estimate of uncertainties associated with the individual spot as well as for groups where the spot data are combined. The repeatability of δ18O measurements is dependent on both the analytical conditions and the choice of the primary reference material. Under optimised conditions, repeatability was often better than 0.4‰ (2s) allowing sample uncertaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…2014, Ávila et al . 2020). The best of the test sample runs gives a spot‐to‐spot reproducibility (±0.3‰, 2 s ), better than that on the reference materials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2014, Ávila et al . 2020). The best of the test sample runs gives a spot‐to‐spot reproducibility (±0.3‰, 2 s ), better than that on the reference materials.…”
Section: Discussionmentioning
confidence: 99%
“…2014, Ávila et al . 2020). For example, a total impact energy of 20kV primary beam produces 20 μm diameter pits when using the CAMECA IMS‐1280, whereas SHRIMP analysis using a 15 kV primary beam results in 25 μm diameter pits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All eleven minerals were considered suitable as RMs. A calcite from the Oka carbonatite complex (Quebec, Canada) was presented 227 228 concluded that Temora 2 was a highly satisfactory RM for O isotope determinations if the provenance of the grains was well established. Repeated analyses over nine sessions and seven different mounts agreed within analytical uncertainty for zircons Temora 2, FC1, R33, QGNG, Plešovice and 91500 when normalised to Mud Tank zircon, which was regarded as a useful QC material with typical repeatability of #0.3& (2SD).…”
Section: Reference Materials and Data Qualitymentioning
confidence: 99%
“…Homogeneity was demonstrated by hundreds of SIMS analyses and the recommended values of δ 13 C VPDB = −5.23 ± 0.06‰ and δ 18 O VPDB = −23.12 ± 0.15‰ were established by conventional IRMS. After measuring O isotope ratios in a range of zircon RMs with high-precision using SHRIMP, Avila et al 228 concluded that Temora 2 was a highly satisfactory RM for O isotope determinations if the provenance of the grains was well established. Repeated analyses over nine sessions and seven different mounts agreed within analytical uncertainty for zircons Temora 2, FC1, R33, QGNG, Plešovice and 91500 when normalised to Mud Tank zircon, which was regarded as a useful QC material with typical repeatability of ≤0.3‰ (2SD).…”
Section: Analysis Of Geological Materialsmentioning
confidence: 99%